Opieka w społeczności nad osobami niepełnosprawnymi - Szluz, Beata (ITP Rzeszów, 2004)
The objective of present article is a reflection over chosen social initiatives realised on behalf of handicapped people on territory of podkarpackie voivodeship. Handicapped people make up a very diversified social group. It is not homogenous group, that is why a wide range of problems associated with it exists. Diversity concerns causes, kinds and degrees of handicap as well as acquired education and experience. They can be people in different age, who have secured care of a family, people who take advantage of complete care of the social institutions (secular or ecclesiastical) as well as homeless people. Gaining of satisfactory level of self-dependence, when one is a handicapped person, requires to take advantage of specialist help in order to overcome a whole series of difficulties or problems associated with the fact itself or with specifity of a certain kind of handicap.
Community care over handicapped people
Keywords: sociology; support; disabled people; social exclusion